Genome-wide association analysis of fleece traits in Northwest Xizang white cashmere goat - Lu, Xiaotian; Suo, Langda; Yan, Xiaochun; Li, Wenze; Su, Yixin; Zhou, Bohan; Liu, Can; Yang, Lepu; Wang, Jiayin; Ji, De; Cuomu, Renqing; Cuoji, Awang; et al. (Frontiers in Veterinary Science, 2024)
Northwest Xizang White Cashmere Goat (NXWCG) is the first new breed of Cashmere Goat in Xizang Autonomous Region. It has significant characteristics of extremely high fineness, gloss and softness. Genome-wide association analysis is an effective biological method used to measure the consistency and correlation of genotype changes between two molecular markers in the genome. In addition, it can screen out the key genes affecting the complex traits of biological individuals. The aim of this study was to analysis the genetic mechanism of cashmere trait variation in NXWCG, to discover SNPs locus and key genes closely related to traits such as superfine cashmere. Additionally, the key genes near the obtained significant SNPs were analyzed by gene function annotation and biological function mining. In this study, the phenotype data of the four traits (cashmere length, fiber length, cashmere diameter and cashmere production) were collected. GGP_Goat_70K SNP chip was used to genotype the ear tissue DNA of the experimental group. Subsequently, Association of phenotype data and genotype data was performed using Gemma-0.98.1 software. Linear mixed model was used for the association study. The results showed that four fleece traits were associated with 18 significant SNPs at the genome level and 232 SNPs at the chromosome level. Through gene annotated from Capra hircus genome using assembly ARS1. A total of 107 candidate genes related to fleece traits were obtained. Combined with Gene Ontology and Kyoto Encyclopedia of Genes and Genomes enrichment analysis, we can find that CLNS1A, CCSER1, RPS6KC1, PRLR, KCNRG, KCNK9 and CLYBL can be used as important candidate genes for fleece traits of NXWCG. We used Sanger sequencing and suitability chi-square test to further verify the significant loci and candidate genes screened by GWAS, the results show that the base mutations loci on the five candidate genes,